2012
DOI: 10.1016/j.physbeh.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Social cues in the expression of sequential alternative reproductive tactics in young males of the peacock blenny, Salaria pavo

Abstract: Phenotypic change in response to variation in environmental cues has been widely documented in fish. Transitions in social dominance, in particular, have been shown to induce a rapid switch in reproductive phenotypes in many species. However, this effect has been mainly studied in adults and focused on behavioural transitions. The way social cues constraint the phenotypic development of juveniles remains poorly studied in fish. We tested the importance of social dominance and density in the phenotypic developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…One possible explanation is that in dominant male rats, where androgen levels in the serum are high ((Lucion et al, 1996; Clarke & Faulkes, 1998; Lofgren et al, 2013) see also (Albert et al, 1986)), behavioral plasticity may be less important than it is for the subordinant male, where serum levels of androgen are substantially lower, and animals need to modify behavior to safely obtain food and water. Indeed, in some species of birds the males with higher testosterone levels breed normally but the males with lower testosterone levels develop alternative reproductive behavior (Fagundes et al, 2012). …”
Section: Dominant Gcs Mossy Fiber Variance and Their Implicationsmentioning
confidence: 99%
“…One possible explanation is that in dominant male rats, where androgen levels in the serum are high ((Lucion et al, 1996; Clarke & Faulkes, 1998; Lofgren et al, 2013) see also (Albert et al, 1986)), behavioral plasticity may be less important than it is for the subordinant male, where serum levels of androgen are substantially lower, and animals need to modify behavior to safely obtain food and water. Indeed, in some species of birds the males with higher testosterone levels breed normally but the males with lower testosterone levels develop alternative reproductive behavior (Fagundes et al, 2012). …”
Section: Dominant Gcs Mossy Fiber Variance and Their Implicationsmentioning
confidence: 99%
“…In some such species, the choice between becoming a “traditional” male and a “sneaker” male appears to be influenced by the social environment [20]. In the peacock blenny ( Salaria pavo ), the outcomes of agonistic interactions among juvenile males are predictive of the decision to become a territory-holding or sneaker male [21]. …”
Section: Continuing Factorsmentioning
confidence: 99%
“…However, Fagundes et al . () demonstrated that the differentiation of the secondary characters typical of nest‐holder males is dependent on the dominance status of the juveniles and their relative body size within a social group, rather than on the absolute body size of males. Accordingly, in the present study, body size is shown to differ between males following the different pathways, but this difference is better explained when considering year variation, thus suggesting that pathways are best described by their relative differences in body size rather than by fixed absolute body size values.…”
Section: Discussionmentioning
confidence: 99%